2020
DOI: 10.5505/pajes.2020.85353
|View full text |Cite
|
Sign up to set email alerts
|

Effect of utilization of mineral admixture on the fresh and hardened properties of air-entrained cement mortars

Abstract: Bu çalışmada, silis dumanı ve uçucu kül kullanımının hava sürükleyici katkılı tekli, ikili ve üçlü çimentolu sistemleri içeren harç karışımlarının taze ve bazı sertleşmiş hal özelliklerine etkisi karşılaştırmalı olarak incelenmiştir. Bu kapsamda tek tip CEM I 42.5R tipi çimento, tek tip polikarboksilat esaslı su azaltıcı katkı, tek tip hava sürükleyici katkı, silis dumanı ve uçucu kül kullanarak farklı kombinasyonlara sahip harç karışımları hazırlanmıştır. Mineral katkı içermeyen kontrol karışımına ilaveten, ü… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…One of the most important parameters affecting the strength and durability performance of 3DPC mixtures is the pore structure. As it is known, the pores are classified as gel, capillary and air voids according to their sizes 34 . Unlike conventional concrete, it was reported that the pores in 3DPC mixtures are not homogeneously dispersed due to the extrusion process 35 .…”
Section: Hardened State Properties Of 3dpc Mixturesmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most important parameters affecting the strength and durability performance of 3DPC mixtures is the pore structure. As it is known, the pores are classified as gel, capillary and air voids according to their sizes 34 . Unlike conventional concrete, it was reported that the pores in 3DPC mixtures are not homogeneously dispersed due to the extrusion process 35 .…”
Section: Hardened State Properties Of 3dpc Mixturesmentioning
confidence: 99%
“…As it is known, the pores are classified as gel, capillary and air voids according to their sizes. 34 Unlike conventional concrete, it was reported that the pores in 3DPC mixtures are not homogeneously dispersed due to the extrusion process. 35 In a study by Cicione et al, 36 using microcomputed tomography (μ-CT) scanning, it was proved that the pore structure of conventional concrete and 3DPC specimens is different (Figure 3).…”
Section: Pore Structurementioning
confidence: 99%
“…In this study, it was determined that 10% MS substitution increased the compressive strength by 4.86% compared to the reference cement (28th day). In terms of chemical effect, as a result of the pozzolanic reaction, the existing gaps in the matrix phase decrease with the conversion of CH to CSH (Güleryüz et al 2020). The positive effect of only 2% NS on the strength is more than 10% MS. (2017) reported that the carbonation resistance of mortar containing 2% NS was much higher than that of 10% MS (Li et al 2017).…”
Section: Characterization Of Ctmentioning
confidence: 99%
“…In order to increase the freeze-thaw resistance of concrete, an air-entraining admixture that will create permanent air spaces is added to the mixture (Sahin, 2003). However, it was reported that the compressive strength of concrete decreases with the addition of airentraining admixture (Guleryuz, 2020). Numerous studies were carried out to improve both the freeze-thaw resistance and the fresh state and mechanical properties of concrete (Erdem & Ozturk, 2012).…”
Section: Introductionmentioning
confidence: 99%